Academic Self-Concept and Motivation in Young Talents of a Private University in Tarapoto - Carranza, Renzo F. (2015)
The objective of this study was to determine the relationship between academic self-concept and academic motivation in young talents (Scholarship 18) at a Private University in Tarapoto city, Peru. The sample was obtained through a probabislitic sampling and there were 92 young talents, being 47,8% male and 52,2% female between 17 and 22 years old. I used a descriptive, correlational and non-experimental design. The sample was evaluated using the AF5 Self-concept Scale (García and Musitu) academic section that consists of 6 items, and the Academic Motivation Scale that consists of 28 items. The psychometric properties of the instruments indicated that they are valid and reliable. Data were processed in SPSS (Statistical Package for the Social Sciences) version 20.0. The results show that there is a direct and highly significant relationship between academic self-concept and academic motivation in young talents (r = .301**, p<.004), which indicates the higher the academic self-concept, the greater the academic motivation.